Environmental durability of glass fiber epoxy composites filled with core–shell polymer particles. (15th February 2016) - Zhong, Yucheng; Joshi, Sunil Chandrakant
Abstract: A manufacturing technique was successfully adopted for incorporating core–shell polymer (CSP) particles into glass fiber reinforced polymer (GFRP) composites. CSP particles were firstly added into inter-ply interfaces during the lamination process. Conventional as well as CSP particle filled GFRP laminates were then cured at 122 °C under high pressure while in a vacuum environment. Good adhesion between the particles and the epoxy matrix was achieved during the curing. GFRP laminates with or without particles were immersed in water at 80 °C for different durations. These conditioned laminates were later subjected to low-velocity impact tests. It was found that the GFRP laminates with CSP particles absorbed more moisture while had less structural defects formed during the conditioning. The CSP particles significantly improved the impact properties of the GFRP laminates. After hygrothermal aging, the beneficial effects brought about by these particles for effectively resisting impact loads diminished. The underlying mechanisms were identified, studied and explained. Graphical abstract: Highlights: CSP particle filled GFRP laminates were fabricated through autoclave curing. CSP particles effectively improved the impact response of GFRP laminates. CSP particles were vulnerable to hygrothermal effects. After hygrothermal aging, the advantages of CSP particles diminished. Impact properties and tensile strength of GFRP composites decreased after aging.